2005
DOI: 10.1002/eat.20158
|View full text |Cite
|
Sign up to set email alerts
|

The perceived onset of dieting and loss of control eating behaviors in overweight children

Abstract: Objective-The current study investigated the self-reported temporal relationships of dieting, binge eating, and overweight in childhood.Method-One hundred five non-treatment-seeking overweight children ages 6-13 years were interviewed with the children's Eating Disorder Examination (ChEDE) and queried regarding dieting, loss of control (LOC) eating, and overweight history. Questionnaires of depressive symptoms, trait anxiety, and parent-reported problems were completed.Results-Sixty percent of the children rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
115
3
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 50 publications
18
115
3
6
Order By: Relevance
“…26 The strength of the present study is its simultaneous attention to all these relevant variables in the same participants. We observed that total ChEAT scores correlated significantly with BMI, corroborating previous studies that found higher scores on the ChEAT questionnaire 27 or other measures of eating pathology 28 among overweight vs. normal-weight children.…”
Section: Discussionsupporting
confidence: 90%
“…26 The strength of the present study is its simultaneous attention to all these relevant variables in the same participants. We observed that total ChEAT scores correlated significantly with BMI, corroborating previous studies that found higher scores on the ChEAT questionnaire 27 or other measures of eating pathology 28 among overweight vs. normal-weight children.…”
Section: Discussionsupporting
confidence: 90%
“…While only a small minority of the sample met criteria for a BED or another form of EDNOS, approximately one-third endorsed loss of control over eating during the last 3 months, which is comparable to previous studies of treatment-seeking overweight youth (Berkowitz et al, 1993;Britz et al, 2000;Goosens et al, in press;Isnard et al, 2003;Levine et al, 2006;Severi et al, 1993). Furthermore, the suggestion that children who endorse any objective binge eating, independent of episode frequency, exhibit increased eating, shape, and weight concerns, is consistent with the existing literature (Berkowitz et al, 1993;Tanofsky-Kraff et al, 2004;Tanofsky-Kraff, Faden, Yanovski, Wilfley, & Yanovski, 2005). We found that the size of the binge episode was important and related to other types of ED pathology-which is in contrast to the findings from two studies of non-treatment-seeking overweight youth that indicate any loss of control eating is significant (Morgan et al, 2002;Tanofsky-Kraff et al, 2004).…”
Section: Article In Presssupporting
confidence: 87%
“…7 Only a small subset of children and adolescents meet full Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV-TR criteria for BED, while the experience of LOC eating and emotional eating seem to be more common. 6,[8][9][10][11][12][13][14] Research indicates that emotional eating and binge eating in children and adolescents are associated with anxiety, sadness, and anger 6,12,15 which has previously been shown in adults. [16][17][18][19][20][21] Overweight children 8,12,14 and adolescents 9,10,22 with LOC eating were shown to experience greater eating-related distress, anxiety, and depressive symptoms than those without LOC eating.…”
Section: Introductionmentioning
confidence: 76%
“…51,52 The Children's Depression Inventory (CDI) is a 26-item self report questionnaire of depressive feelings for ages [8][9][10][11][12][13][14][15][16]. Internal consistency of the total score of the German version is high, convergent, and discriminant validity have been demonstrated.…”
Section: Methodsmentioning
confidence: 99%